The Effect of Perceived Ease of Use, Free Shipping Program, and E-Servicescape on E-Satisfaction (Study on Alfagift Application Users in Surabaya) - Angela Clarisa Wijaya; Sonja Andarini (Universitas KH. Abdul Chalim Mojokerto, 2026)
Businesses evolve, and retail is no exception. Companies must have the right strategy amid the digital era and understand consumer needs to win the competition in an increasingly tight market. One of the things that companies must pay attention to is consumer habits in shopping online. This study aimed to determine and analyze the effect and significance of perceived ease of use, free shipping program, and e-Servicescape simultaneously and partially on e-satisfaction in Alfagift application users in Surabaya. Quantitative is the type of research used in this study. The number of samples needed is 150 respondents who were taken using purposive sampling which is part of the non-probability sampling technique. Primary data is the type of data used, which is taken from distributed questionnaires. Multiple linear regression analysis is a data analysis technique in this study. The research findings show that: (1) perceived ease of use, free shipping program, and e-Servicescape simultaneously have an effect and are significant on e-satisfaction; (2) perceived ease of use and e-Servicescape partially have an effect and are significant on e-satisfaction; and (3) free shipping program partially has no effect and is not significant on e-satisfaction.